The Hydrogen-Coupled Oligopeptide Membrane Cotransporter Pept2 is SUMOylated in Kidney Distal Convoluted Tubule Cells - Aroankins, Takwa S.; Murali, Sathish K.; Fenton, Robert A.; Wu, Qi (Frontiers in Molecular Biosciences, 2021)
Protein post-translational modification by the Small Ubiquitin-like MOdifier (SUMO) on lysine residues is a reversible process highly important for transcription and protein stability. In the kidney, SUMOylation appears to be important for the cellular response to aldosterone. Therefore, in this study, we generated a SUMOylation profile of the aldosterone-sensitive kidney distal convoluted tubule (DCT) as a basis for understanding SUMOylation events in this cell type. Using mass spectrometry-based proteomics, 1037 SUMO1 and 552 SUMO2 sites, corresponding to 546 SUMO1 and 356 SUMO2 proteins, were identified from a modified mouse kidney DCT cell line (mpkDCT). SUMOylation of the renal hydrogen-coupled oligopeptide and drug co-transporter (Pept2) at one site (K139) was found to be highly regulated by aldosterone. Using immunolabelling of mouse kidney sections Pept2 was localized to DCT cells in vivo. Aldosterone stimulation of mpkDCT cell lines expressing wild-type Pept2 or mutant K139R-Pept2, post-transcriptionally increased Pept2 expression up to four-fold. Aldosterone decreased wild-type Pept2 abundance in the apical membrane domain of mpkDCT cells, but this response was absent in K139R-Pept2 expressing cells. In summary, we have generated a SUMOylation landscape of the mouse DCT and determined that SUMOylation plays an important role in the physiological regulation of Pept2 trafficking by aldosterone.